Advances in acute pancreatitis management: From guidelines to clinical practice - Huseynov, Amil; Çezik, Azamet (The European Research Journal, 2025)
Objectives: This study aimed to evaluate current management strategies and early outcomes in patients with acute pancreatitis (AP) to provide insights into effective practices and contribute to the discourse on optimizing AP care. Methods: A retrospective observational study was conducted on 350 AP patients admitted to Kanuni Sultan Süleyman Training and Research Hospital between January 2015 and December 2022. Data were extracted from electronic medical records, including demographics, clinical presentation, laboratory findings, imaging results, treatment strategies, and outcomes. Patients were assessed for severity using the Revised Atlanta Classification and Bedside Index for Severity in Acute Pancreatitis (BISAP) scores, and management protocols included controlled fluid resuscitation, pain management, nutritional support, selective antibiotic use, and endoscopic interventions. Results: Of 350 patients (male: 54%, mean age: 50 years), 79.7% had mild AP, 14.9% moderately severe AP, and 5.4% severe AP. Goal-directed fluid resuscitation and early nutritional support were implemented, with early oral feeding initiated in 81.4% of cases. Antibiotics were used in 20% of patients with confirmed or suspected infections, and Endoscopic retrograde cholangiopancreatography (ERCP) was performed in 24.6% of patients with biliary pancreatitis. The mean hospital stay was 7, 14, and 21 days for mild, moderately severe, and severe AP, respectively. Intensive care unit (ICU) admission was required for 8.6%, and in-hospital mortality was 2%. Recurrence within six months occurred in 9.1% of cases. Conclusions: management strategies adhering to current guidelines led to favorable early outcomes, including reduced complications and a high six-month survival rate (98%). Future multicenter studies are recommended to confirm these findings and assess long-term outcomes.